A New Strategy for the Detection of Chicken Infectious Anemia Virus Contamination in Attenuated Live Vaccine by Droplet Digital PCR. (16th May 2019) - Li, Qiuchen; Zhang, Yubiao; Meng, Fanfeng; Jiang, Hui; Xu, Guanlong; Ding, Jiabo; Zhang, Yawen; Dong, Guiwei; Tian, Sibao; Chang, Shuang; Zhao, Peng
Abstract : Chicken infectious anemia virus ( CIAV ) causes the atrophy of bone marrow hematopoietic and lymphoid tissues in chicks, leading to huge economic losses all over the world. The using of attenuated vaccine contaminated with CIAV increased the mortality and the pathogenicity of other diseases in many farms. However, it is difficult to detect the CIAV contamination by general detection technology due to the extremely low dose of CIAV in vaccines. In this study, we established a new method called droplet digital Polymerase Chain Reaction ( ddPCR ) to detect CIAV contamination of vaccines more sensitively and accurately. The lowest detection limitation of this method is 2.4 copies of CIAV plasmid or CIAV contamination at 0.1 EID50 /1000 feathers in vaccines without any positive signals of other viruses. Besides, the sensitivity of ddPCR is 100 times greater than that of conventional PCR and 10 times greater than that of real-time PCR. The ddPCR technique is more sensitive and more intuitive. Therefore, it could be valuable for the detection of CIAV contamination in vaccines.